Politik Uang dalam Pemilukada Kabupaten Mandailing Natal Tahun 2010 - Ahmad Afif Azhari (Dinamika Politik, 2012)
This is a study about money politics in local election of Mandailing Natal Regency 2010. The focus is to describe what are the reason money politics can be done in Aek Marian Village. This study find three reasons that make money politics can be done. The first, decrease of law enforcement and morality; The second, weakness of the political party to give political education; The third, phenomenon of poverty and pragmatism. The method of this study is descriptive-qualitative that purpose to explain the case detailly.Keyword: Money politics, political behaviour, rationality of the voter.